The comparision of glybenclamide and metformin-loaded bacterial cellulose/gelatin nanofibres produced by a portable electrohydrodynamic gun for diabetic wound healing - YAVUZ, AYŞE NUR; ERTAŞ, BÜŞRA; ÇAM, MUHAMMET EMİN (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
Wound dressings made from natural polymers are an important aspect of biomaterials. Protein-based materials are less likely to instigate an immunogenic response and have the capacity to degrade in vivo, also without triggering an inflammatory response. Therefore, gelatin (GEL) was chosen and combined with bacterial cellulose (BC) to produce nanofibres and the potential of an all-natural polymer construct was determined. GEL and BC were successfully electrospun with metformin (Met) and glybenclamide (Gb) using a portable, point of need electrospinning set up. The virgin fibre group exhibited a significant effect on the proliferation of L929 (mouse fibroblast) cells but all fibre samples can safely be applied on wound site without risk of cytotoxicity. According to the results obtained by animal tests, the GEL-BC-Gb group showed better recovery than the GEL-BC-Met group. Diabetic wounds treated with GEL-BC-Met were characterized by moderate re-epithelialization and partially organized granulation tissue. Moderate to complete re-epithelialization and well-formed granulation tissue were observed in diabetic wounds treated with GEL-BC-Gb. The histologic scores obtained on day 14 confirmed that the GEL-BC-Gb group played a stronger wound-healing role compared to the GEL-BC-Met group. The highest decrease of TNF-alpha level was observed in the GEL-BC-Gb group at the end of the experiment but there is no significant difference between drug-loaded fibre groups. Therefore, topical administration of ma and Gb in a sustained release form has a high potential for diabetic wound healing with high bioavailability and fewer systemic side effects but Gb showed better improvement according to the results of the animal tests.
Keywords: Bacterial cellulose; Gelatin; Wound dressings; Oral antidiabetic agents; Drug release; Portable electrohydrodynamic gun; SKIN; PHENOTYPE; GELATIN